Studies on production of low calorie lassi - D, Brahamani; Y, Kotilinga Reddy; V, Vijaygeetha; Rao, K N (Indian Journal of Dairy Science, 2020)
Lassi containing the artificial sweeteners was compared with control sample containing sugar for quality parameters. Aspartame was used at 80, 90 and 100 ppm, and sucralose at 20, 25 and 30 ppm levels for total replacement of sugar during production of low calorie lassi. Based on the physico-chemical and sensory quality parameters, lassi added with 90 ppm aspartame and 25 ppm sucralose were found to be acceptable compared to control lassi. To achieve the mouthfeel of the finished product as that of control lassi, a bulking agent i.e. sorbtiol was added at three different levels i.e. 7, 7.5 and 8.0% respectively to the selected levels of sweetener. It was found that 7.5 per cent sorbitol level was more suitable than the lassi prepared with 7.0 and 8.0 levels of sorbitorl with respect to physico-chemcial and sensory quality. Satisfactory quality low calorie lassi was prepared by using artificial sweeteners viz . sucralose and asparatame along with sorbitol.